S95 Role of ifnβ in modulating innate immunity of primary bronchial epithelial cells (PBECs) during respiratory infection. (December 2018) - Spalluto, CM; Watson, A; McCrae, C; Cellura, D; Burke, H; Cunoosamy, D; Freeman, A; Hicks, A; Huhn, M; Ostridge, K; Staples, K; Vaarala, O; et al.
Abstract : Introduction: There is evidence that an impaired innate immunity, caused by a defect in IFNβ expression in response to viral infections could be linked with exacerbations in asthmatic and COPD patients. So far the administration of inhaled IFNβ upon patients reporting cold or flu symptoms has failed to prevent exacerbations. This highlights the need to understand the dynamics between viral infection and the IFN system to be able to design effective antiviral therapies. Objective: To investigate the dynamics of induction and maintenance of anti-viral responses mediated by exogenous IFNβ in the context of influenza infection, we set up an in-vitro model with PBECs from healthy and COPD. Cells were cultured in media containing IFNβ 50IU/ml either for 16 hour or for 2 hour pre or post infection with H3N2 Influenza A/Wisconsin/67/2005. We also investigated the duration of the IFNβ response by culturing PBECs for up to 1 week prior to infection. Proportion of infected cells (%NP1 + ) was measured by flow cytometry and qPCR was used to measure viral RNA and anti-viral gene expression. Multiplex ELISA (MSD) was used to measure inflammatory cytokines. Results: Administration of IFNβ 16 hour prior to infection reduced%NP1 + PBECs from a median of 27% to 9.2% (p<0.001) and there was 200x less viral RNA in the supernatant of cells conditioned with IFNβ compared to untreated (p<0.05). The IFNβ effect was still evident 24 hour after administration (7.9% NP1 + ), maintained up to 48 hour (16.7%, p<0.05) and lost at 1 week (26.1%). This effect was mirrored by the upregulation of interferon stimulated genes including MX1, OAS1 and RIG-I. The expression of negative regulatory genes: BLIMP1, SOCS1, SOCS3 and USP18 also followed a similar trend. Furthermore IFNβ did not induce a general production of inflammatory cytokine production but reduced IL-1β expression after infection with influenza. Conclusions: This primary epithelial model demonstrates that IFNβ pre-treatment may be suitable to prevent infection. Moreover these results highlight the need to understand the interactions between the virus and the IFN system to be able to identify optimal time of clinical delivery.